Hospital Strike Women. Unions and Public Sector Conflict - McPherson, Kathryn (Labour / Le Travail, 1993)
The article reviews the book, "Hospital Strike: Women, Unions and Public Sector Conflict," by Jerry White.
Keywords: BOOKS -- Reviews; HOSPITAL Strike: Women, Unions & Public Sector Conflict (Book); Labor disputes; Nonfiction; WHITE, Jerry

Workshop on Canadian Working-Class History, Victoria, May 1990 - McPherson, Kathryn; Conley, James R.; Creese, Gillian; Seixas, Peter; Piva, Michael J.; Bernard, Elaine; Leger, Raymond (Labour / Le Travail, 1991)
Presents seven papers from the workshop: "Feminist Reflections on the Writing of Canadian Working Class History in the 1980s" by Kathryn McPherson, "Peculiarities of British Columbians" by James R. Conley, "The British Columbia Working Class: New Perspectives on Ethnicity/Race and Gender" by Gillian Creese, "Teaching Working Class History in B.C." by Peter Seixas, "Labour Programmes: A Challenging Partnership" by Elaine Bernard, "Labour Historians and Unions: Assessing the Interaction" by Michael J. Piva, and "The New Brunswick Experience" by Raymond Leger.
Keywords: Canada; History; LABOR market; Labor Unions; Labor movement; Man-woman relationships; STRIKES & lockouts; Social classes; WORKING class in literature; WORKING class women; Working class